(untitled) (Global Journal of Science Frontier Research, 2019)
Fungi are associated with heavy losses of seeds, fruits, grains, vegetables, and other plant products in transit and storage rendering them unfit for human consumption. The effect of synthetic fungicides on humans is hazardous, hence the need to find a safer means of control. A research was conducted in Hong Local Government Area of Adamawa State of Nigeria (the most prominent groundnut farming community in the state). The following molds were associated with postharvest groundnut rot in the seven districts of Hong local government area in July 2016: Aspergillus niger, Aspergilus flavus, Penicillium chrysogenum, Rhizopus stolonifer, Paecilomyces lilacinus, Pseudallescheria boydii, Cylindrocarponl ichenicola, and Scedosaporium prolificans. Therefore, the research sought to assess the management of rot using plant extracts of mahogany. Control trials were carried out using the extracts of root of mahogany. The growth of pathogens both in-vitro and in-vivo was significantly reduced by the plant extracts.